On capturing human agency and methodological interdisciplinarity in socio-hydrology research - Yu, David J.; Haeffner, Melissa; Jeong, Hanseok; Pande, Saket; Dame, Juliane; Di Baldassarre, Giuliano; Garcia-Santos, Glenda; Hermans, Leon; Muneepeerakul, Rachata; Nardi, Fernando; Sanderson, Matthew R.; Tian, Fuqiang; et al. (Hydrological sciences journal, 2022)
Socio-hydrology has expanded and been effective in exposing the hydrological community to ideas and approaches from other scientific disciplines, and social sciences in particular. Yet it still has much to explore regarding how to capture human agency and how to combine different methods and disciplinary views from both the hydrological and the social sciences to develop knowledge. A useful starting ground is noting that the complexity of human-water relations is due to interactions not only across spatial and temporal scales but also across different organizational levels of social systems. This calls for consideration of another analytical scale, the human organizational scale, and interdisciplinarity in study methods. Based on the papers published in this journal’s Special Issue Advancing Socio-hydrology over 2019-2022, this paper illuminates how the understanding of coupled human-water systems can be strengthened by capturing the multi-level nature of human decision making and by applying an interdisciplinary multi-method approach.
Gesehen am 01.02.2023